Multivariate Analysis of Nurses' Performance in the Implementation PNCM in Inpatient Room Installation of Dr. H. Moch. Ansari Saleh Banjarmasin - Rida Millati (Health Media, 2019)
Implementation of Patient Nursing Care Model (PNCM) with team method in Inpatient Room Installation of Dr. H. Moch Ansari Saleh Banjarmasin was not yet optimal. This research was to analyse factors that influence on there and used cross sectional approach. Population 256 nurses with non probability sampling incidental, with sample amounted to 92 respondents. Statistics analyze used SEM Smart PLS 3.0. The determinants of the performance of PNCM implementation in this study are individual facto, education, knowledge, motivation, leadership, and reward and job design. The results of research are leadership; job design and motivation give significant influence on the performance of nurses in the implementation of PNCM, where individual factor period did not significantly influence. Nurse motivation came from need and support conducive environment fulfilled. Effective leadership by head ward increasing employee trust so made increased nursing performance. Job design that clear can nurse more easily done their job.